Developing a holistic decision support framework: From production logistics to sustainable freight transport in an urban environment. (December 2021) - Hauge, Jannicke Baalsrud; Birkie, Seyoum Eshetu; Jeong, Yongkuk
Highlights: How to overcome challenges related to decision making in urban production logistics. Identify the factors from the recent research project and systematic literature review. Facilitate the development of simulation models for urban production logistics. Abstract: In recent years, policy makers as well as urban logistics and transport research have investigated how to reduce environmental impact from transportation in urban areas. Therefore, many new frameworks that can help a specific actor in its decision making process at a certain decision making level (i.e., business or policy level) have been implemented and published. However, the first screening of existing literature did not reveal frameworks that can be used across different decision making levels. This limits the possibility for actors using the same infrastructure but not necessarily co-operate to discuss how the actions and needs of each actor of different decision making levels mutually influence each other. This paper first presents an outcome of a literature review and analysis of existing research project results before. It combines these to a multi-layer framework that can enhance collaborative decision-making and seamless aggregation of performance measures such as environmental impact from multiple transportation activities in and around urban areas. For this multi-layer framework, factors are identified, and possible relationships across the various layers are indicated. The field of application is the area near urban manufacturing sites and specifically addressing all actors that share on regulate infrastructure relevant to last mile inbound logistics. The source of data is project databases as well as for the literature review research databases. The methodology applied is a combination of a literature review based on database entries and a snowball approach. The article also presents how the framework can be prototypically implemented in participatory simulations using a simplified example. Potential usage for establishing holistic urban mobility structures is also discussed.